Comparison between resonant-column and bender element tests on three types of soils (2013)
The bender element (BE) test is used in laboratory to obtain the shear wave velocity of soils. Different execution and interpretation techniques have been proposed. However, there is not a specialized technique with an adequate level of accuracy and reproducibility to be adopted as a standard. Several factors affect the reliability of this method, mainly because of complex phenomena of wave propagation in the small volume of the specimen. Three type of soils were tested by Resonant-Column (RC) and two BE test methods (BETD and BEFD). Results suggest that in non-plastic soils the stiffness tends to be underestimated compared with the stiffness obtained by the RC test. The BETD method could be affected by the soil plasticity. The frequency domain method (BEFD) had less agreement with respect to the RC test.